Engineering of Corynebacterium glutamicum for growth and succinate production from levoglucosan, a pyrolytic sugar substrate - Kim, Eun-Mi; Um, Youngsoon; Bott, Michael; Woo, Han Min (Blackwell, 2015)
Thermochemical processing provides continuous production of bio-oils from lignocellulosic biomass. Levoglucosan, a pyrolytic sugar substrate C6H10O5 in a bio-oil, has been used for ethanol production using engineered Escherichia coli. Here we provide the first example for succinate production from levoglucosan with Corynebacterium glutamicum, a well-known industrial amino acid producer. Heterologous expression of a gene encoding a sugar kinase from Lipomyces starkeyi, Gibberella zeae or Pseudomonas aeruginosa was employed for levoglucosan conversion in C. glutamicum because the wild type was unable to utilize levoglucosan as sole carbon source. As result, expression of a levoglucosan kinase (LGK) of L. starkeyi only enabled growth with levoglucosan as sole carbon source in CgXII minimal medium by catalyzing conversion of levoglucosan to glucose-6-phosphate. Subsequently, the lgk gene was expressed in an aerobic succinate producer of C. glutamicum, strain BL-1. The recombinant strain showed a higher succinate yield (0.25 g g(-1)) from 2% (w/v) levoglucosan than the reference strain BL-1 from 2% (w/v) glucose (0.19 g g(-1)), confirming that levoglucosan is an attractive carbon substrate for C. glutamicum producer strains. In summary, we demonstrated that a pyrolytic sugar could be a potential carbon source for microbial cell factories.